2021
DOI: 10.1126/sciadv.abd7924
|View full text |Cite
|
Sign up to set email alerts
|

Hoxa10 mediates positional memory to govern stem cell function in adult skeletal muscle

Abstract: Muscle stem cells (satellite cells) are distributed throughout the body and have heterogeneous properties among muscles. However, functional topographical genes in satellite cells of adult muscle remain unidentified. Here, we show that expression of Homeobox-A (Hox-A) cluster genes accompanied with DNA hypermethylation of the Hox-A locus was robustly maintained in both somite-derived muscles and their associated satellite cells in adult mice, which recapitulates their embryonic origin. Somite-derived satellite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Recently Hox10 expression and epigenetic methylation events at the Hox-A locus were found to mediate the topographical distribution of differential responsiveness by adult muscle stem cells (Yoshioka et al 2021 ). This paper recalled earlier reports on cranial muscles that present continuous “remodeling” through satellite cell turnover and fusion into undamaged muscle fibers above levels seen in limb muscle fibers (e.g., McLoon and Wirtschafter 2002 , 2003 ; McLoon et al 2004 ).…”
Section: The Current Contextmentioning
confidence: 99%
“…Recently Hox10 expression and epigenetic methylation events at the Hox-A locus were found to mediate the topographical distribution of differential responsiveness by adult muscle stem cells (Yoshioka et al 2021 ). This paper recalled earlier reports on cranial muscles that present continuous “remodeling” through satellite cell turnover and fusion into undamaged muscle fibers above levels seen in limb muscle fibers (e.g., McLoon and Wirtschafter 2002 , 2003 ; McLoon et al 2004 ).…”
Section: The Current Contextmentioning
confidence: 99%
“…Here, we show that both HOXA and HOXC gene family are expressed in myofibers, and their expression levels differs between leg muscles. Yoshioka, Nagahisa et al (2021) also showed expression of HOX genes in adult human muscle tissues. Yet, Terry, Zhang et al (2018) concluded that the expression pattern of Hox genes in adult muscles is insufficient to explain the mRNA expression diversity in adult mouse skeletal muscles.…”
Section: Molecular Diversity Between Muscles In Different Anatomical ...mentioning
confidence: 88%
“…Recently, much attention has been given to the role of Hox proteins in adult muscle stem cells (MuSCs), also known as satellite cells, able to regenerate adult muscles upon injury ( Machado et al, 2017 ; Evano et al, 2020 ; Yoshioka et al, 2021 ). It is now accepted that depending on the anatomical position of the muscle, satellite cells display heterogeneity in their proliferative and regenerative properties ( Ono et al, 2010 ).…”
Section: Somatic/skeletal Musculaturementioning
confidence: 99%
“…It is now accepted that depending on the anatomical position of the muscle, satellite cells display heterogeneity in their proliferative and regenerative properties ( Ono et al, 2010 ). Searching for underlying molecular determinants, Hox-A and Hox-C clusters were found to have different methylation profiles and thus be differentially expressed in adult muscles and their satellite cells derived from somites, compared to the ones derived from the cranial mesoderm ( Evano et al, 2020 ; Yoshioka et al, 2021 ). Knowing that the cranial-derived, Hox-free, satellite cells display higher regenerative capacity than the limb, Hox-expressing satellite cells, an appealing possibility is that Hox could be involved in this process ( Evano et al, 2020 ).…”
Section: Somatic/skeletal Musculaturementioning
confidence: 99%
See 1 more Smart Citation